The Effect of Mindfulness on the Family Well-Being in Mother who Works as a Nurse - Arni Nur Rahmawati; Meidiana Dwidiyanti; Muhammad Mu'in (IJNP (Indonesian Journal of Nursing Practices), 2019)
Background: Mothers who work as nurses are one of the vulnerable groups and are at risk of imbalance of roles in work and family due to multiple roles. The dual role requires working mothers to carry out their duties as mothers and wives at home, while at work can carry out duties as nurses. This is a stressor for mothers who work as nurses in adapting to their roles. This condition can reduce family well-being by decreasing the relationship of family structure, the ability of the role and function of the mother in the family, and the ability to prevent family vulnerability. Interventions that can be carried out to improve the family well-being are Mindfulness STOP (Stop, Take a Breath, Observed, Proceed). Objective: This study aimed to determine the effect of mindfulness on family well-being in mothers who work as nurses at X Hospital Semarang. Method: The design of this study was a quasi-experiment pre-post test with a control group, involving 52 respondents obtained by purposive sampling technique based on the results of inclusion criteria screening, consisting of 26 respondents in the intervention group (given Mindfulness exercises) and 26 respondents in the control group (without treatment). Mindfulness STOP is given for 4 sessions totaling 4 meetings in 1 month. Data analysis used Wilcoxon and Mann-Whitney tests. Results: The results of this study are mindfulness effect on improving family well-being in the intervention group of mothers who work as nurses with a p-value of 0.000. Conclusion: The conclusion of this research is mindfulness can improve family well-being in mothers who work as nurses. Mindfulness is recommended as an intervention to improve employee well-being, especially in carrying out roles in the family and as a basis for further research